MANAJEMEN PROGRAM PEMBIASAAN KEAGAMAAN BINA SISWA IMAN DAN TAKWA (BINWA IMTAK)) DALAM UPAYA PENGUATAN KARAKTER SISWA - Ade Tutti Rokhayati Rosa; Endang Sawitri; Tia Mutia; Hadiyanti; Enden Sirojudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study addresses the challenges of managing religious habituation programs in strengthening students’ character at the junior secondary school level. The research aims to describe the management of the Bina Siswa Iman dan Bina Siswa Iman Dan Takwa (BINWA IMTAK)) religious habituation program through a collaborative research approach. The study was conducted at SMPN 1 Purwakarta and SMPN 2 Karangtengah Cianjur using a qualitative descriptive methodology. Data were collected through document analysis and semi-structured interviews with school leaders and teachers. Data analysis was carried out through data reduction, data display, and conclusion drawing using the Plan–Do–Check–Act (PDCA) management framework. The findings indicate that program planning in both schools is aligned with the schools’ vision and mission, program implementation is carried out consistently according to each school’s context, evaluation focuses on monitoring changes in students’ religious behavior and discipline, and follow-up actions emphasize strengthening a religious school culture. The study concludes that the success of Bina Siswa Iman Dan Takwa (BINWA IMTAK), program is not determined by uniformity of activities, but by effective program management, contextual adaptation, and consistent role modeling by educators